Graph Tuple Transformation - Kreowski, Hans-Jörg; Kuske, Sabine (Electronic Communications of the EASST, 2013)
Graph transformation units are rule-based devices to model and compute relations between initial and terminal graphs. In this paper, they are generalized to graph tuple transformation units that allow one to combine different kinds of graphs into tuples and to process the component graphs simultaneously and interrelated with each other. Moreover, one may choose some of the working components as inputs and some as outputs such that a graph tuple transformation unit computes a relation between input and output tuples of potentially different kinds of graphs rather than a binary relation on a single kind of graphs.